Influencer Ferry Irwandi’s Communication Strategy In Framing Social Issues and Audience Responses On Tiktok In 2025 - Ahmad Aswari Hasibuan; Irma Yusriani Simamora (Jurnal Ilmu Sosial dan Humaniora, 2026)
TikTok has evolved into a digital communication platform that serves not only as a source of entertainment but also as a medium for disseminating social issues that stimulate public discourse. One of the content creators who consistently addresses such issues is Ferry Irwandi, whose content covers topics related to economics, politics, public policy, and humanitarian issues. This study aims to analyze Ferry Irwandi’s communication strategies in framing social issues, identify the categories of social issues presented in his content, and examine audience responses in the comment section as part of the dynamics of public discourse on TikTok. This study employed a qualitative approach using the content analysis method. The research corpus consisted of four TikTok videos selected through purposive sampling from Ferry Irwandi’s uploads throughout 2025. The units of analysis included the video content, captions, and 40 audience comments, while the data were analyzed through the stages of transcription, coding, categorization, and interpretation conducted by a single researcher. The findings reveal that Ferry Irwandi consistently applies communication strategies characterized by the use of clear and straightforward language, logical argumentation, conceptual simplification, strong opening hooks, solution-oriented criticism, and emotional appeals tailored to the characteristics of each social issue. Audience responses demonstrate varying patterns of acceptance and rejection depending on the context of the issues discussed, indicating that the comment section functions as an interactive space for exchanging perspectives on social media. The findings also demonstrate a relationship between message packaging strategies, the characteristics of social issues, and the dynamics of audience engagement within digital public discourse. This study contributes to the development of digital communication studies, particularly in understanding influencer communication strategies in framing social issues and fostering audience engagement on social media.